Differential local tissue permissiveness influences the final fate of GPR17‐expressing oligodendrocyte precursors in two distinct models of demyelination. Issue 5 (9th February 2018) - Coppolino, Giusy T.; Marangon, Davide; Negri, Camilla; Menichetti, Gianluca; Fumagalli, Marta; Gelosa, Paolo; Dimou, Leda; Furlan, Roberto; Lecca, Davide; Abbracchio, Maria P.
Abstract: Promoting remyelination is recognized as a novel strategy to foster repair in neurodegenerative demyelinating diseases, such as multiple sclerosis. In this respect, the receptor GPR17, recently emerged as a new target for remyelination, is expressed by early oligodendrocyte precursors (OPCs) and after a certain differentiation stage it has to be downregulated to allow progression to mature myelinating oligodendrocytes. Here, we took advantage of the first inducible GPR17 reporter mouse line (GPR17‐iCreER T2 xCAG‐eGFP mice) allowing to follow the final fate of GPR17 + cells by tamoxifen‐induced GFP‐labeling to unveil the destiny of these cells in two demyelination models: experimental autoimmune encephalomyelitis (EAE), characterized by marked immune cell activation and inflammation, and cuprizone induced demyelination, where myelin dysfunction is achieved by a toxic insult. In both models, demyelination induced a strong increase of fluorescent GFP + cells at damaged areas. However, only in the cuprizone model reacting GFP + cells terminally differentiated to mature oligodendrocytes, thus contributing to remyelination. In EAE, GFP + cells were blocked at immature stages and never became myelinating oligodendrocytes. We suggest these strikingly distinct fates be due to different permissiveness of the local CNS environment. Based on previously reported GPR17 activation by emergency signals (e.g., Stromal Derived Factor‐1), we propose that a marked inflammatory milieu, such as that reproduced in EAE, induces GPR17 overactivation resulting in impaired downregulation, untimely and prolonged permanence in OPCs, leading, in turn, to differentiation blockade. Combined treatments with remyelinating agents and anti‐inflammatory drugs may represent new potential adequate strategies to halt neurodegeneration and foster recovery. Main Points: GPR17+ OPCs react to EAE but are not able to reach terminal maturation. GPR17+ OPCs expand their pool and effectively contribute to remyelination in the cuprizone model. Maturation of GPR17+ precursors depends on the local permissiveness.